Juridical Review of Legal Protection for Registered Trademark Rights Owners: Case Study Decision Number 242 K/Pdt.Sus-HKI/2022 - Fahmi Fairuzzaman; Safwah Adea Nugrahani (Universitas Muhammadiyah Surakarta, 2023)
Brand disputes are a matter that still frequently occurs in Indonesia. As in the case of the ARRA + LUKISAN brand and the COCO ARRA brand. ARRA + LUKISAN filed a lawsuit at the Commercial Court because its brand had been imitated and was substantially similar. The formulation of the problem in this research is the first to file principle in terms of the MIG Law and legal protection for first to file data collectors in the case of Decision Number 242 K/Pdt.Sus-HKI/2022. The method applied is normative juridical. The results of research regarding the first to file principle in the MIG Law are that it provides legal protection for the first registrant. Furthermore, regarding legal protection for the first trademark registrant in the case of Decision Number 242 K/Pdt.Sus-HKI/2022, namely the ARRA + LUKISAN trademark, obtained through the results of a decision at the cassation stage which has permanent legal force, namely approving the cassation request by the Cassation Petitioner, canceling the Decision. Commercial Court at the Central Jakarta District Court Number 70/Pdt.Sus-HKI/Merek/2019/PN Niaga Jkt. Pst, then instructed the co-defendants to cancel the registration of the COCO ARRA mark.